Kurikulum Pendidikan Anak Usia Dini Dalam Keluarga Di Masa Pandemi Covid-19 - Prawening, Cesilia; Khomsiyatun, Umi; Riska Nofianti, Farhati; Triana (Jurnal Tumbuh Kembang Anak Usia Dini, 2023)
The COVID-19 pandemic has had a major impact on the education system and governance, the learning environment of students during the pandemic has to switch to a home with an online learning system. This of course also has an impact on changing the learning curriculum both at school and at home. This study aims to describe and analyze the curriculum of early childhood education in the family during the COVID-19 pandemic. This research is a type of phenomenological research, where researchers try to describe events in the field. Data were collected by interview and observation techniques. The data analysis techniques used are reduction, data presentation and fermentation as well as drawing conclusions. The results of this study show that in the preparation of the child's education curriculum while at home, parents can refer to four aspects, namely, aspects of child growth and development, aspects of play, aspects of learning, aspects of family. Meanwhile, the resulting curriculum is in the form of a new order for children's learning activities while at home.